Preliminary performance assessment of a novel on-shore system recovering energy from tidal currents. (15th August 2018) - Barbarelli, S.; Florio, G.; Amelio, M.; Scornaienchi, N.M.
Highlights: A novel on-shore system collecting energy from tidal currents is proposed. The energy harvesting is provided by a submerged blade moving up and down. The vertical alternate motion is transferred to ground through a four-bar linkage. The four-bar linkage acts a piston pump which provides pressure to a reservoir. A turbine, closing the hydraulic circuit, is fed by the air-pressurized reservoir. Abstract: An innovative system for recovering energy from tidal currents is proposed. The system is composed of a blade immersed in sea water and connected to a vertical bar which, moving up and down under the action of the sea current, transfers energy to a double effect pump. The latter feeds a pressurized reservoir providing a water flow rate, at suitable pressure, to a hydraulic turbine. The basic configuration involves a four-bar linkage connecting the vertical bar and the piston pump. The system can be employed in all the sites whose seabed quickly deepens and whose tidal currents are parallel to the coast. In this paper, the authors provide a methodology for designing the system, once found the bathymetry of the chosen site and the field of variation of the tidal current velocities, taking into account the morphology of the costal boundary layer. A case study, developed for the Calabrian site of Punta Pezzo (Strait of Messina – Italy), demonstrated the technical feasibility.